Customers' perception of Air Asia's facebook marketing activities: A case study of the aviation industry in Malaysia - Chan, Tak Jie; Monteiro, Cassandra Nicole; Tengku Mohd Azzman, Tengku Siti Aisha (UPM, 2021)
The airline industry has become one of the most crucial industries that contribute to the nation’s economy. In times of the unforeseen pandemic, this crucial economic sector has been one that was severely impacted. Thus, this research aims to examine the dimensions of Facebook marketing activities perceived as prominent by the consumers of Air Asia. A quantitative survey research design was conducted whereby a total of 137 valid responses was achieved through the purposive sampling technique. The results indicated that trendiness was the most prominent Facebook marketing activities perceived as prominent by the customers. The results of this research may be used by the airline company to further examine the importance of each social media marketing activities and formulated their branding marketing strategy. Future studies may expand this study by testing various outcome variables that may contribute to the marketing communication and advertising scholarship.